P-N ўтишли диодларнинг Ферми Квази сатҳи ва волть – ампер характеристикасига микотўлқин таъсири - Гулямов, Г; Шаҳобиддинов, Б.Б; Мажидова, Г.Н; Қурбонова, Д.О (SCIENCE and SOCIETY, 2022)
The quasi-levels of electrons and holes are studied in semiconductors in a strong microwave field. It is shown that the- se changes in the Fermi quasi-level strongly affect the current-voltage characteristic of a semiconductor diode with a p-n junction.
Keywords: electromotive force (EMF) current-voltage (CV) characteristic microwave field (SHF) hot electrons; quasi-Fermi levels (QFL)